2005
DOI: 10.1042/cs20040174
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytokines in cardiovascular diseases: a focus on endothelial responses to inflammation

Abstract: Complex cellular and inflammatory interactions are involved in the progress of vascular diseases. Endothelial cells, upon exposure to cytokines, undergo profound alterations of function that involve gene expression and de novo protein synthesis. The functional reprogramming of endothelial cells by cytokines is of importance especially in patients with chronic vascular inflammation. The intercellular network of dendritic cells, T-lymphocytes, macrophages and smooth muscle cells generates a variety of stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
250
2
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(261 citation statements)
references
References 96 publications
3
250
2
6
Order By: Relevance
“…Firstly, that an elevated Creactive protein identifies tumours capable of producing significant amounts of proinflammatory cytokines, in particular interleukin-6 (Kinoshita et al, 1999;McKeown et al, 2004) and therefore with the potential for more rapid growth of tumour cells (Jee et al, 2001;Trikha et al, 2003). Also, that an elevated C-reactive protein identifies those patients with T-lymphocyte impairment (Maccio et al, 1998;Canna et al, 2005) or patients with a proangiogenic environment (Kofler et al, 2005;Xavier et al, 2006) allowing unrestrained tumour growth and dissemination. Clearly, both these tumour and host mechanisms may be related and required for the greater malignant potential associated with an elevated C-reactive protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, that an elevated Creactive protein identifies tumours capable of producing significant amounts of proinflammatory cytokines, in particular interleukin-6 (Kinoshita et al, 1999;McKeown et al, 2004) and therefore with the potential for more rapid growth of tumour cells (Jee et al, 2001;Trikha et al, 2003). Also, that an elevated C-reactive protein identifies those patients with T-lymphocyte impairment (Maccio et al, 1998;Canna et al, 2005) or patients with a proangiogenic environment (Kofler et al, 2005;Xavier et al, 2006) allowing unrestrained tumour growth and dissemination. Clearly, both these tumour and host mechanisms may be related and required for the greater malignant potential associated with an elevated C-reactive protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Other properties attributed to IL-8 include the chemoattraction of T lymphocytes [8], angiogenic activity (reviewed in Ref. [11]), stimulation of histamine release from basophils (reviewed in Ref. [12]).…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and animal studies have demonstrated that elevated atherogenic lipoproteins lead to: (1) an increase in the adhesion of monocytes and T lymphocytes to the endothelial surface; (2) an increase in the migration of monocytes and T lymphocytes into subendothelial spaces; and (3) provision of the lipid core for the transformation of monocytes/macrophages into foam cells, which secrete several plasma inflammatory markers [8,9].…”
Section: Introductionmentioning
confidence: 99%